2014
DOI: 10.3402/tellusb.v66.22716
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water uptake on the aerosol particle light scattering coefficients of the Central European aerosol

Abstract: A B S T R A C TThe influence of aerosol water uptake on the aerosol particle light scattering was examined at the regional continental research site Melpitz, Germany. The scattering enhancement factor f(RH), defined as the aerosol particle scattering coefficient at a certain relative humidity (RH) divided by its dry value, was measured using a humidified nephelometer. The chemical composition and other microphysical properties were measured in parallel. f(RH) showed a strong variation, e.g. with values between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 57 publications
(69 reference statements)
4
67
1
Order By: Relevance
“…However, the differences are mostly under 10 % and therefore the discussion is focused on 550 nm wavelength in this study. Similar results were obtained by Zieger at a regional continental research site in Melpitz, Germany (Zieger et al, 2014). …”
Section: Wavelength Dependence Of the Scattering Enhancement Factor Fsupporting
confidence: 87%
See 2 more Smart Citations
“…However, the differences are mostly under 10 % and therefore the discussion is focused on 550 nm wavelength in this study. Similar results were obtained by Zieger at a regional continental research site in Melpitz, Germany (Zieger et al, 2014). …”
Section: Wavelength Dependence Of the Scattering Enhancement Factor Fsupporting
confidence: 87%
“…The absolute values of both slopes (1.2 for f (85 %) vs. organic mass fraction and 0.96 for f (85 %) vs. inorganic mass fraction) were much lower than those (3.1 and 2.2, respectively) measured at Melpitz, Germany (Zieger et al, 2014). This may partly be due to the higher organic (or lower inorganic) content at Lin'an.…”
Section: The Relationship Of Scattering Enhancement Factor With Chemicontrasting
confidence: 38%
See 1 more Smart Citation
“…Continental aerosols (e.g. f (85 %, 550 nm) ≈ 1.8-2.8; Zieger et al, 2012Zieger et al, , 2014Fierz-Schmidhauser et al, 2010b;Koloutsou-Vakakis et al, 2001;Sheridan et al, 2001) and urban aerosols (e.g. f (85 %, 550 nm) ≈ 1.3-1.6; Titos et al, 2014b;Zieger et al, 2011;McInnes et al, 1998;Fitzgerald et al, 1982) are observed with intermediate values.…”
Section: Introductionmentioning
confidence: 96%
“…It is required, for example, for closure experiments (consistency checks between different measurement methods involving an aerosol model, e.g., Wiegner et al, 2009;Gasteiger et al, 2011b;Müller et al, 2012;Bell et al, 2013;Ma et al, 2014;Zieger et al, 2014;Düsing et al, 2018), radiative transfer studies (e.g., Otto et al, 2009;Emde et al, 2010), the inversion of remote-sensing measurements (e.g., Dubovik et al, 2006;Gasteiger et al, 2011a;Müller et al, 2016), the inversion of in situ data (e.g., Weinzierl et al, 2009;Szymanski et al, 2009;Kassianov et al, 2014), aerosol layer visibility simulations (e.g., Weinzierl et al, 2012), dynamic aerosol transport models (e.g., Heinold et al, 2007;Balzarini et al, 2015), aerosol characterization (e.g., Gasteiger et al, 2017;Che et al, 2018;Zhuang et al, 2018), and solar energy (e.g., Polo et al, 2016;Kosmopoulos et al, 2017).…”
Section: Applicationsmentioning
confidence: 99%